Student Community Service based on Creative Digital Collaboration Project (SCSCDC) to Empower Rural Communities against Covid-19 - Aulia Fatimatuz Zahra; Andrea Salsalova; Arini Arum Madzani; Djono -; Nur Fatah Abidin (Pancaran Pendidikan, 2021)
The outbreak of Covid-19 has created a great change in the implementation of Kuliah Kerja Nyata (KKN) or Student Community Service Program (SCS) in Indonesia. This article promotes the idea of Student Community Service based on Creative Digital Collaboration Project as a collective movement to empower the community against Covid-19. The method of research was a Mixed Method. The research participants were 25 university students who took a part in SCS Covid-19 in 2020. The data were collected through online questionnaires and interviews, then analyzed in quantitative and qualitative approaches. The result shows that the university has provided a platform to implement SCS during a pandemic. The obstacle lies in the lack of collaboration and social challenges in society. Students as the agent of change to create villages resistant Covid-19. The authors believe that this idea can become a future model of SCS during pandemic Covid-19.